Selective 2′-hydroxyl acylation analyzed by primer extension (SHAPE): quantitative RNA structure analysis at single nucleotide resolution - Wilkinson, Kevin A; Merino, Edward J; Weeks, Kevin M (Nature protocols, 2006)
Selective 2′-hydroxyl acylation analyzed by primer extension (SHAPE) interrogates local backbone flexibility in RNA at single-nucleotide resolution under diverse solution environments. Flexible RNA nucleotides preferentially sample local conformations that enhance the nucleophilic reactivity of 2′-hydroxyl groups toward electrophiles, such as N-methylisatoic anhydride (NMIA). Modified sites are detected as stops in an optimized primer extension reaction, followed by electrophoretic fragment separation. SHAPE chemistry scores local nucleotide flexibility at all four ribonucleotides in a single experiment and discriminates between base-paired versus unconstrained or flexible residues with a dynamic range of 20-fold or greater. Quantitative SHAPE reactivity information can be used to establish the secondary structure of an RNA, to improve the accuracy of structure prediction algorithms, to monitor structural differences between related RNAs or a single RNA in different states, and to detect ligand binding sites. SHAPE chemistry rarely needs significant optimization and requires two days to complete for an RNA of 100–200 nucleotides. Note: In the version of this article initially published online, the value for the pH range in the second paragraph on page 2 was incorrect; it should have read 7.5–8.2. In addition, two sentences were included that should have been removed from page 1. These errors have been corrected in all versions of the article.